Locus coeruleus tonic upregulation increases selectivity to inconspicuous auditory information in autistic compared to non-autistic individuals: a combined pupillometry and electroencephalography study - Bast, Nico; Ahmad, Jumana; Mason, Luke; Jones, Emily J. H.; Matyjek, Magdalena; Polzer, Leonie; Luckhardt, Christina; Müller, Anna Katharina; McAlonan, Grainne M.; Banaschewski, Tobias; Baumeister, Sarah; Loth, Eva; et al. (Molecular autism, 2025)
Sensory processing requires selectivity to salient sensory input. Many autistic individuals report different sensory processing, which has been associated with altered sensory selectivity. The locus-coeruleus norepinephrine (LC-NE) system modulates the neuronal gain of sensory input, which represents a neurophysiological mechanism of sensory selectivity. In autistic individuals, we hypothesized that LC-NE tonic upregulation reduces sensory selectivity and underlies different sensory processing. Autistic (n = 139) and non-autistic (n = 98) individuals were assessed during a passive auditory oddball task with pupillometry and electroencephalography. For every trial, a baseline pupil size (BPS) assessed LC-NE tonic activity that coincides with current arousal, while a stimulus-evoked pupillary response (SEPR) assessed LC-NE phasic activity that estimated sensory selectivity. Electroencephalography assessed amplitudes of mismatch negativity (MMN-amp) that estimated pre-attentive change detection as a brain-activity readout of sensory selectivity. Measures were modeled between groups within the task by combining Frequentist and Bayesian approaches. Across groups, higher BPS was associated with more negative MMN-amp to standards and oddballs. A more negative MMN-amp to standards was associated with a higher SEPR to standards. Controlling for these associations, autistic versus non-autistic individuals showed a higher SEPR in response to standards. In addition, a positive association of BPS and SEPR to standards was specific to autistic individuals. With task progression, autistic versus non-autistic individuals showed a higher initial increase and subsequently steeper decrease of BPS. This was supported by Bayesian posterior distribution estimates. A short trial duration required concatenating trials to epochs and applying a linear-time invariant filter to capture the slow pupil changes. Without an LC-NE manipulation, we cannot rule out that pupil changes are evoked by other cortical pathways than the LC-NE. Across groups, LC-NE tonic upregulation is emphasized as a general mechanism that un-specifically increases pre-attentive change detection to all sensory stimuli, which then increases sensory selectivity to frequent stimuli. In autistic individuals, different sensory processing is characterized by increased sensory selectivity to frequent stimuli. This is likely caused by an LC-NE tonic upregulation. It associates autistic sensory processing with increased arousal upregulation that increases sensory selectivity to inconspicuous auditory information.
Gesehen am 10.11.2025
Mitglieder der The EU-AIMS LEAP group: Jumana Ahmad, Sara Ambrosino, Bonnie Auyeung, Tobias Banaschewski, Simon Baron-Cohen, Nico Bast, Sarah Baumeister, Christian F. Beckmann, Sven Bölte, Thomas Bourgeron, Carsten Bours, Michael Brammer, Daniel Brandeis, Claudia Brogna, Yvette de Bruijn, Jan K. Buitelaar, Bhismadev Chakrabarti, Tony Charman, Ineke Cornelissen, Daisy Crawley, Flavio Dell’Acqua, Guillaume Dumas, Sarah Durston, Christine Ecker, Jessica Faulkner, Vincent Frouin, Pilar Garcés, David Goyard, Lindsay Ham, Hannah Hayward, Joerg Hipp, Rosemary Holt, Mark Johnson, Emily J.H. Jones, Prantik Kundu, Meng-Chuan Lai, Xavier Liogier D’ardhuy, Michael V. Lombardo, Eva Loth, David J. Lythgoe, René Mandl, Andre Marquand, Luke Mason, Maarten Mennes, Andreas Meyer-Lindenberg, Carolin Moessnang, Declan G.M. Murphy, Bethany Oakley, Laurence O’Dwyer, Marianne Oldehinkel, Bob Oranje, Gahan Pandina, Antonio M. Persico, Barbara Ruggeri, Amber Ruigrok, Jessica Sabet, Roberto Sacco, Antonia San José Cáceres, Emily Simonoff, Will Spooren, Julian Tillmann, Roberto Toro, Heike Tost, Jack Waldman, Steve C.R. Williams, Caroline Wooldridge & Marcel P. Zwiers